2018
DOI: 10.1016/j.jalz.2018.06.1353
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of amyloid quantitation with florbetapir standardized uptake value ratios to the Centiloid scale

Abstract: These findings may allow improved tracer-independent amyloid quantitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 20 publications
9
141
0
1
Order By: Relevance
“…Eq. 5) derived based on raw SUVrs without RSF PVC was similar to the published equations from a recent paper [16]. The difference is attributable to variation in image acquisition protocols and quantification procedures.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Eq. 5) derived based on raw SUVrs without RSF PVC was similar to the published equations from a recent paper [16]. The difference is attributable to variation in image acquisition protocols and quantification procedures.…”
Section: Resultssupporting
confidence: 68%
“…Previously, Laudau et al [31] compared these two tracers using florbetapir data collected approximately 1.5 years after PiB imaging and found a correlation between 0.86 and 0.95 depending on the quantification method used. More recently, Navitsky et al [16] reported a florbetapir‐to‐PiB SUVr correlation of approximately 0.95. These results are in agreement with ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CL results below this threshold should provide reassurance that patients are unlikely to have Alzheimer's disease. This is reasonably concordant with the findings of Navitsky and colleagues, who determined a threshold of 24.1 CL with florbetapir for CERAD amyloid plaque classification of moderate or frequent vs sparse or none, in 59 individuals [21]. This is also concordant with the Centiloid analysis by Dore and colleagues of a florbetaban phase III post-mortem study in 66 individuals, which yielded a threshold of 19 CL for the same categorisation [22].…”
Section: Fig 1 Centiloid Results and "High" Vs "Low" C Score Categoriessupporting
confidence: 89%
“…All YC subjects were younger than 45 years of age (mean ± SD: 27 ± 4.3 y), the sample had equal gender distribution (M/F: 6/7), and low APOE4 positivity prevalence (9 negative, 1 positive, 3 unknown). The data was originally acquired to serve as a YC reference data set for scaling of global Florbetapir-PET signal to the standardized Centiloid scale (Navitsky et al, 2018a) and is freely available on the Global Alzheimer Association Interactive Network website (GAAIN; http://www.gaain.org/centiloid-project). As reported previously (Grothe et al, 2017;Navitsky et al, 2018a), written informed consent was obtained for all study participants and/or authorized representatives, and data collection and sharing were performed in accordance with the ethical standards of the institutional and/or national research committees (http://adni.…”
Section: Participantsmentioning
confidence: 99%